Nursing Mental Health and Community Concepts - Christman, Elizabeth; Ernstmeyer, Kimberly (Open textbook library., 2022)
This textbook is an open educational resource with CC-BY licensing developed specifically for prelicensure nursing students. The e-book and downloadable versions are free. Affordable print versions are published in collaboration with XanEdu and available on Amazon and in college bookstores. Content is based on the Wisconsin Technical College System (WTCS) statewide nursing curriculum for the Nursing Mental Health and Community Concepts course (543-110), the NCLEX-RN Test Plan, 1 and the American Psychiatric Nurses Association Education Council’s Crosswalk Toolkit: Defining and Using Psychiatric-Mental Health Nursing Skills in Undergraduate Nursing Education. 2 Mental health and community health concepts are discussed while emphasizing stress management techniques, healthy coping strategies, referrals to community resources, and other preventative interventions. Nursing care for individuals with specific mental health and substance use disorders is examined, and the nurse’s role in community health needs assessments and caring for vulnerable populations is introduced. The e-book is free and can be viewed online or downloaded as a PDF or other formats for offline use. Affordable print versions are also published in collaboration with XanEdu and are available on Amazon and in college bookstores.